Javanese Lexical Variation of Cirebon Dialect in Pabuaran and Ciperna Region - Eva utami Durahman; Dinny Sofiyani; Yosi Ayu Pratiwi; Fani Setiani (Universitas Teknokrat Indonesia, 2019)
This study highlights the lexical differences phenomena in Pabuaran and Ciperna region which is located in Cirebon Regency of West Java. This study aims: 1) to describe the Javanese lexical variations of Cirebon dialect in Pabuaran and Ciperna region, 2) and to find out whether those variations are dialect, subdialect, or only speech level differences of Cirebon dialect itself by utilizing dialectometric method. The result shows that there are 108 lexical differences in the form of pronouns (10), nouns (26), verbs (44), adjectives (14), and adverb (14) in Pabuaran and Ciperna region. This result is obtained by using 207 words Swadesh List and 144 additional words submitted as questions to the local people. Furthermore, after being calculated by dialectometric method, it can be concluded that those lexical variation in Pabuaran and Ciperna are chategorized as subdialect rather than dialect or speech level differences.Keywords: Cirebon dialect, Javanese language, lexical variations